THE IMPACT OF PROFESSIONALISM AND COMPETENCE ON AUDITOR PERFORMANCE WITH WORK MOTIVATION AS MODERATION VARIABLES IN PUBLIC ACCOUNTING FIRM MEDAN CITY - Shabrina Tri Asti Nasution; Thezar Fiqih Hidayat Hasibuan; Devi Ayu Putri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The accountability of these financial statements will make stakeholders believe in the company's management to provide the best for the company. Financial statement accountability will all stakeholders work together and work hard to develop the company to be bigger, therefore good auditor performance is strongly demanded so that all parties interested in financial reports do not make wrong decisions and policies for their companies. The purpose of this study is to see the impact of professionalism and competence on auditor performance which is moderated by the work motivation. Data collection is done by survey method with questionnaires. The population of this study is the Auditor in Public Accounting Firm Medan City. Primary data is obtained through the spreading of questionnaires. Hypothesis testing in this study used Moderating Regression Analysis. The results of this study indicate that professionalism and competence have a positive and significant effect on auditor performance, and work motivation is a moderating variable that can strengthen the effect of professionalism on auditor performance, but work motivation is not a variable that can moderate the effect of competence on auditor performance.